The History of St. Stephen's Anglican Church, Lachine, Quebec, Canada, 1822-1956 - Merchant, George (s.é., 1956)
Keywords: Anglicans; Lachine; Protestants; St. Stephen's (paroisse)

Collège Sainte-Anne de Lachine, 1861-1986: 125 ans d'éducation au service des jeunes - Serres, Jeannine (Soeurs de Sainte-Anne, 1987)
Keywords: Collège Sainte-Anne; Communautés religieuses; Lachine; Soeurs de Sainte-Anne

Le comportement de certains habitants de Lachine aux environs de 1689 - Séguin, Robert-Lionel (Bulletin des recherches historiques, 1954)
Keywords: Lachine

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

From Meritocracy to Seniority: Shifting Masculine Aesthetics Among blue-collar workers in Montréal Lachine - Desforges, Exan Yuen (Université Concordia, 2008)
Keywords: Lachine; Quartiers

Fourrures, eau-de-vie et absolution: réseaux sociaux, économiques et politiques à Lachine, 1670-1680 - Martin, Catherine (Université de Sherbrooke, 2014)
Keywords: Fourrure; Lachine

The Lachine Strike of 1843 - Pentland, H. C. (Canadian Historical Review, 1948)
Keywords: Grèves; Irlandais; Lachine (canal)

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

L'Hôpital de Lachine célèbre son centenaire en 2013 / The Lachine Hospital Celebrates its 100th Anniversary in 2013 (Héritage Dorval, 2013)
Keywords: Hôpitaux

L'escadrille 686 Dorval/Lachine célèbre son 65e anniversaire de fondation/686 squadron Dorval/Lachine celebrates its 65th anniversary - Hébert, Michel (Héritage Dorval, 2023)
Keywords: Aviation; Dorval

Église des Saints-Anges de Lachine à Ville LaSalle - Bélisle, Jean (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: LaSalle; Patrimoine; Églises

Mère Marie-Elise, religieuse de Sainte-Anne, préfète générale des études, 1860-1933 - Marie-Rollande, Soeur (Soeurs de Sainte-Anne, 1940)
Keywords: Communautés religieuses; Marie-Elise, Mère; Soeurs de Sainte-Anne

Mère Marie-Irène, préfète générale des études, 1896-1914, secrétaire-générale, 1914-1931 - Marie-Rollande, Soeur (Soeurs de Sainte-Anne, 1941)
Keywords: Communautés religieuses; Marie-Irène, Mère; Soeurs de Sainte-Anne

Les soeurs de Sainte-Anne. Un siècle d'histoire. Tome I 1850-1900 - Marie-Jean-De-Pathmos, Soeur (Soeurs de Sainte-Anne, 1950)
Keywords: Communautés religieuses; Soeurs de Sainte-Anne

Martyre du silence: mère Marie-Anne, fondatrice des Soeurs de Sainte-Anne (1809-1890) - Nadeau, Eugène (Éd. Sainte-Anne, 1956)
Keywords: Blondin, Esther (Marie-Anne, Mère); Communautés religieuses; Soeurs de Sainte-Anne

Quatre filles fondatrices - Nantel Bergeron, Dominique (Histoire Québec, 2024)
Keywords: Famille; Femmes; Lachine

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Mouvement syndical et mobilisation pour l’emploi: renouvellement des enjeux et des modalités d’action - Fontan, Jean-Marc; Klein, Juan-Luis (Politique et sociétés, 2000)
Keywords: Confédération des syndicats nationaux; Dominion Bridge; Fédération des travailleurs et travailleuses du Québec (FTQ); Lachine

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde